Acoustic, and Categorical, Deviation Effects are Produced by Different Mechanisms: Evidence from Additivity and Habituation. Issue 1 (3rd April 2022) - Littlefair, Zoe; Vachon, François; Ball, Linden J.; Robinson, Nick; Marsh, John E.
ABSTRACT: Sounds that deviate, acoustically or semantically, from prevailing auditory backgrounds disrupt ongoing mental activity. An acoustic deviant is held to capture attention, but doubt has been cast on the attentional nature of the semantic, categorical deviation effect. Unlike the acoustical deviation effect, which is typically amenable to top-down cognitive control, the categorical deviation effect is impervious to top-down influences.To shed further light on the mechanisms underpinning acoustic and categorical deviance, we compared the disruptive impact produced by acoustic deviants (change of voice), categorical deviants (change of category) and combined deviants (change of voice and category) randomly inserted into a to-be-ignored sequence while participants performed a visual-verbal serial recall task.In Experiment 1, all deviants disrupted recall, however combined deviants produced greater disruption than acoustic deviants alone. In Experiment 2 only the disruption produced by an acoustic deviant diminished over the course of the experiment. The acoustic and categorical deviation effects combined additively to disrupt performance (Experiment 1) and habituation was only observed for the acoustic deviation effect (Experiment 2).These results gel with the idea that attentional responses to deviants, and habituation thereof (Experiment 2), is a key component of acoustic but not categorical deviation effects. Taken together, these findings support recent assertions that independent mechanisms drive acoustic and categorical deviation effects.